FEATURES OF STRUCTURE OF SKIN OF HAIRY DEPARTMENT OF HEAD OF MEN AT ANDROGENIC DEFLUXION - Tikhonova О.A. (World of Medicine and Biology, 2013)
Utillized by us universal innovative method of morphological researches, provided the receipt of original information, which not only complement the known facts but also in more depth expose principles of device of skin of hairy department of head of men in a norm and after an androgenic pelade. In the process of androgenic pelade degradation undergo foremost интрадермальные hair follicles which склерозирование of hair bags is in. In the reticulated layer of дермы substituted for degrading hair follicles соединительнотканной стромой. Complete loss of hairs at an androgenic defluxion, results in компенсаторно-приспособительному reorganization of skin of hairy department of head, which is expressed in a substitution in the hypodermis of loose fibred connecting fabric fatty fabric, vast excrescence in all of layers of skin of blood vessels which the venous prevail among, and also, in the considerable increase of concentration of oil-glands in the reticulated layer of дермы. In spite of complete loss of hairs at an androgenic pelade, герминативные ephithelial elements, being sources formations of thin /abortive/ hairsprings array patterns of which, are saved in the skin of hairy department of head, hidden in the layer of oil-glands. On the basis of the actual findings, in sew on position is grounded work, that loss of hairs at an androgenic defluxion, filled in due to the physiological hypertrophy of other tissue constituents of skin.